Optimization of the Learning Process of Handball Exercises - Ibragimov Alisher Karomatovich; Ravshanov Amirali Alimardon o’g’li (Research Parks Publishing LLC, 2022)
The article raises the problem of optimization of the educational process in physical education classes at the handball department. Among the students of 1-2 courses aged 17-20 years old, who go in for handball, priority motives were identified that played a major role in the choice of this sport out of fifteen others presented at the Faculty of Physical Education of BSU.